2021
DOI: 10.5937/fme2103549h
|View full text |Cite
|
Sign up to set email alerts
|

IPG as a new method to improve the agility of the initial analysis of the inventive design

Abstract: TRIZ method has long proven its value without appearing to the industrial world as inevitable. Design researchers have therefore addressed the limitations of the TRIZ method and have overcome them with more systematic approaches. Among these, the Inventive Design Method (IDM) has been the subject of several articles and put into practice in the industry. It is considered an improvement over TRIZ but still suffers from some drawbacks in terms of the time-consuming nature of its implementation. We focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Nevertheless, the indicators for assessing these various types of networks are (1) centrality (closeness-centrality), (2) density, (3) cohesion index and (4) structural holes. Recently [ 121 ], proposed the inverse problem graph (IPG) method in which five types of problems were predefined from the initial analysis of the inventive design. This method was inspired by inventive design method (IDM).…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Nevertheless, the indicators for assessing these various types of networks are (1) centrality (closeness-centrality), (2) density, (3) cohesion index and (4) structural holes. Recently [ 121 ], proposed the inverse problem graph (IPG) method in which five types of problems were predefined from the initial analysis of the inventive design. This method was inspired by inventive design method (IDM).…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Thus, in the end, this study managed to narrow down the number of inventive design approaches shown in Figure 1 which have attracted the attention of researchers and organizations in the last two decades and are useful for generating SCs in the concept generation phase. Also, this study identified and focused on the inventive design approaches on which modern tools have been applied, like TRIZ and its extensions such as IDM, inverse problem graph (IPG) [10], etc.…”
Section: Background and Prior Workmentioning
confidence: 99%
“…Design of Experiments (DoE) [16] is a very common and robust approach to modeling and representing the design parameters. Nevertheless, it still suffers from certain limitations.…”
Section: Introductionmentioning
confidence: 99%